Analisis Kemampuan Pemahaman Kognitif Dan Kesulitan Belajar Matematika Konsep “Logika” Dengan Model Pembelajaran Daring - Andri Anugrahana (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2021)
This study aims to describe the results of the analysis of cognitive comprehension abilities and learning difficulties in mathematics logic subject using the online learning model for PGSD students at Sanata Dharma University. The research method used is descriptive research method. The research involved PGSD students of Sanata Dharma University in 2020/2021 with data collection techniques and information through a student response questionnaire instrument and cognitive ability test questions using Google form. The results of the study explain that the implementation of online learning regarding the concept of logic has used applications such as WhatsApp, LMS, zoom, google meet, google form. Analysis of students' cognitive abilities is measured by tests that have met the cognitive dimension standards according to Bloom's Taxonomy and the results of student completeness that reach above the KKM are 38%, while the number of students below the KKM reaches 62%. Student difficulties can be divided into two types, namely conceptual difficulties and technical difficulties in implementing online learning.